Aplikacje mobilne typu fit — planowanie posiłków i dieta pod kontrolą technologii - Dejnaka, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
More and more people in Poland begin to check in detail what products they buy and what they consume every day. Some of these people are on a diet that reduces weight or try to match/plan meals to meet the needs of their body (e.g. a sports training plan). Mobile applications come to their aid, as they facilitate the above processes related to meal planning and diet. The aim of the article is to present the results of qualitative research and critical analysis of mobile applications available on the market in the field of meal planning, introducing a reduction diet and maintaining it. The article also attempts to answer the following questions: What is the assessment and expectations for fitness mobile applications by users? Are meal planning and diets under the control of technology a trend or a necessity?
Keywords: aplikacje mobilne; dieta; kalkulator kalorii; skład produktu; technologia